Association of IRAK1 Gene Polymorphism rs3027898 With Papillary Cancer Restricted to the Thyroid Gland: A Pilot Study - CHATZIKYRIAKIDOU, ANTHOULA (In Vivo, 2019)
Background/Aim: The incidence of thyroid cancer has increased predominantly due to an increase in papillary thyroid cancer (PTC). Alteration of toll-like receptor function has been reported to play a crucial role in carcinogenesis. The aim of the present study was to investigate predisposition to PTC associated with genetic markers of toll-like receptor and interleukin-1 receptor pathways involving nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-ĸB) stimulation. Specifically, the study focused on the following genes: interleukin-1 receptor-associated kinase 1 (IRAK1, rs3027898), NF-ĸB inhibitor alpha (NFΚBIA, rs696), NF-ĸB subunit 1 (NFΚB1, rs28362491), and microRNA-146a (miR-146a, rs2910164). Patients and Methods: Forty-eight unrelated patients with papillary cancer restricted to the thyroid gland and 93 healthy volunteers were enrolled in the study. Results: A strong statistically significant difference was observed between patients with PTC and controls for IRAK1 rs3027898 variant. When the statistical analysis was replicated taking into account patient’s sex, the rs3027898 A allele was revealed to be the risky variant in males. Conclusion: Additional studies in larger groups of patients of various origins are needed to validate these preliminary findings.